Landscapes of Watermills: A Rural Cultural Heritage Perspective in an East-Central European Context - Alexandru Dragan; Remus Crețan; Mădălina Ionela Terian (Heritage)
Recent studies in rural heritage tourism have highlighted that watermills could stand as an important part of the pre-industrial tourism heritage. We contribute to rural heritage tourism by basing our study on the perceptions of tourists and local officials on the Rudăria Watermills, Romania. Based on survey and interview data, we document the strengths and limits of local watermills for tourism and describe the entrepreneurial agents involved in path development. Our findings point to the important role played by a local NGO in developing a path for tourism for the watermills, as well as the active involvement of local authorities and other local cultural leaders in including the mills in national and international tourism circuits.